PENERAPAN SISTEM PAKAR UNTUK IDENTIFIKASI ANAK BERKEBUTUHAN KHUSUS MENGGUNAKAN METODE RULE BASED SYSTEM - Yumarlin Yumarlin MZ; Hanang Indrianta (Informasi Interaktif, 2022)
Every parent wants the presence of a child. The child expected by parents is a perfect child without any flaws. In fact, there is no human being without flaws. Humans are not the same as one another. Whatever the circumstances, humans are uniquely created by the Creator. Understanding of children with special needs is biological, psychological, socio-cultural. Children with special needs are children who require special treatment because of developmental disorders and abnormalities experienced by children.The purpose of this study is related to designing and developing an automated expert system application for the identification of children with special needs in detecting the characteristics seen in children, which can help parents or the general public, so that they can find out early on the child's condition. This application uses a rule based system method, namely forward chaining which is a heuristic method used for application development in this study.Based on the results of trials on 20 respondents using the system usability scale (SUS) method, it obtained an average score of 69.37. These results indicate that the expert system for identifying children with special needs in detecting the characteristics seen in children that has been designed and built is categorized as good and feasible to use.Keywords: Sistem Pakar, Anak  Berkebutuhan Khusus,Rule Based System.